Formula and preparation method of carbon dioxide absorbent
By combining the formulation of modified nanocellulose, metal organic frame and other components, an efficient CO2 absorber is prepared, which solves the problems of high cost and poor stability of CO2 absorber in the prior art, and achieves efficient and economical CO2 capture and Separation effect.
Patent Information
- Application Number
- CN202411415140.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-17
AI Technical Summary
Existing CO2 absorbers have high cost, poor stability and weak scalability, making it difficult to effectively capture and separate carbon dioxide in industrial applications.
The formulation of modified nanocellulose, metal organic frame, graphene, 1-ethyl-3-methylimidazole glycine ionic liquid, activated carbon, alkali metal salt and sodium dodecyl sulfate through specific preparation Methods A highly efficient carbon dioxide absorber was prepared to improve the contact area and absorption efficiency of the absorber with CO2, and maintain stable performance under harsh working conditions.
It significantly improves the absorption capacity and absorption efficiency of CO2, reduces the cost of the overall absorbent, is suitable for CO2 capture from various industrial emission sources, and maintains stable absorption performance under harsh operating conditions, reducing frequent replacement due to performance attenuation cost and environmental pressure.
Smart Images

Figure CN119318860A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to CO 2 The invention relates to the field of absorption technology, and in particular to a formula of a carbon dioxide absorbent and a preparation method thereof. Background Art
[0002] With the acceleration of global industrialization, carbon dioxide (CO 2 ) emissions continue to increase, leading to serious greenhouse effect and climate change. Therefore, effectively capturing and storing CO 2 It has become the focus of global attention.
[0003] In many CO 2 Among capture technologies, chemical absorption has attracted much attention due to its high efficiency and strong operability. 2 Chemical reactions occur, absorbing and separating it from the gas mixture. However, conventional CO 2 Absorbents, such as ethanolamine (MEA) solutions, suffer from some significant disadvantages.
[0004] Although MEA solution has a higher CO 2 The absorption efficiency is high, but its regeneration energy consumption is large, it is easy to corrode equipment, and its stability is poor. In addition, MEA solution has a high absorption efficiency. 2 The absorption capacity is limited and a large amount of solution circulation is required, resulting in high operating costs.
[0005] In recent years, new materials and technologies such as ionic liquids, nanomaterials and composite absorbents have been widely used in CO 2 The absorption field has shown great potential. Ionic liquids have the advantages of low volatility, good thermal stability, and strong designability, but they often have problems such as high cost and high viscosity. Nanomaterials such as metal organic frameworks have high specific surface area and porosity, which can provide abundant CO 2 adsorption sites, but in practical applications there may be challenges such as insufficient mechanical strength and difficulty in large-scale preparation.
[0006] Composite absorbents combine different types of absorbents, hoping to give full play to their respective advantages and achieve more efficient, economical and stable CO 2 However, most of the new CO 2 Absorbents are still in the laboratory research stage, and there are still many problems to be solved in actual industrial applications, such as cost, stability, scalability, etc.
[0007] In order to solve the above problems, the present invention provides a formula of a carbon dioxide absorbent and a preparation method thereof. Summary of the invention
[0008] The purpose of the present invention is to provide a formula of a carbon dioxide absorbent and a preparation method thereof to solve the problems raised in the background technology:
[0009] Existing CO 2 The absorbent has high cost, poor stability and weak scalability.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] A formula of a carbon dioxide absorbent comprises, by weight percentage, 5-15% of modified nanocellulose, 10-20% of a metal organic framework, 1-5% of graphene, 10-20% of 1-ethyl-3-methylimidazolium glycine salt ionic liquid, 1-10% of activated carbon, 5-20% of diethylenetriamine, 5-10% of an alkali metal salt, 0.1-0.5% of sodium dodecyl sulfate, 20-40% of water and 10-20% of ethanol.
[0012] Preferably, 0.02-0.20% of an acid-base indicator is also added to the formula.
[0013] Preferably, the alkali metal salt is prepared by mixing nitrate and carbonate, the molar ratio of the nitrate to the carbonate is 1.5-2; and the number of the nitrate and the carbonate is not less than two.
[0014] Preferably, the nanocellulose in the modified nanocellulose is extracted from cellulose-rich waste plants by TEMPO oxidation.
[0015] Preferably, the modified nanocellulose is modified by using Lactobacillus plantarum as a modification tool.
[0016] A method for preparing a formula of a carbon dioxide absorbent comprises the following steps:
[0017] S1: Preparation of biomaterial-modified nanocellulose:
[0018] S1.1: The cellulose-rich plant waste was vacuum dried at 105°C for 2 h, ground by a grinder, and the plant powder was soaked in 10% K 2 OH solution, and heated at 60°C, and then fully washed with distilled water, and then dried at 70°C, and then the dried matter was immersed in a hydrogen peroxide solution, and then fully washed with distilled water, and then dried at 70°C to obtain plant powder;
[0019] S1.2: The plant powder was added to water at a material-liquid ratio of 1:80-120 g / mL, and then 0.02 g of pyrroline nitroxide free radical and 0.2 g of nitrogen-containing six-membered heterocyclic catalyst were added. The reaction was started by adding 10-15% hydrogen peroxide solution under ultrasonic stirring, and 0.5% K2 OH solution to adjust the pH value and keep it at 10.3-10.7 without consuming K 2 In the presence of OH, ethanol is added to stop the reaction, and then stirred for 15 to 25 minutes. The final product is washed with deionized water by continuous centrifugation at 3000 to 3500 r / min for 10 to 15 minutes until it is neutral; the recovered supernatant becomes a nanocellulose water suspension, which is freeze-dried to obtain cellulose nanofibers;
[0020] S1.3: sterilizing the MRS culture medium with an autoclave at 120-125°C, activating and culturing Lactobacillus plantarum at 37°C, adding the cellulose nanofibers and the bacterial activation solution to the sterile culture solution, and then subjecting the culture solution to differential centrifugation at 3000-3500 r / min to obtain modified cellulose nanofibers;
[0021] S2: Synthesize metal-organic frameworks and combine them with modified nanocellulose;
[0022] S3: 1-ethyl-3-methylimidazolium glycine salt ionic liquid, diethylenetriamine, graphene, alkali metal salt, water and ethanol were mixed according to the formula ratio, and the complex prepared in S2 was added to the mixed solution, and stirred at room temperature for 1 to 3 hours to prepare CO 2 Absorbent.
[0023] Preferably, S2 is specifically as follows:
[0024] S2.1: Dissolve 2-4.5g of cellulose in a mixed solution of sodium hydroxide / urea / water in a mass ratio of 7:12:81 precooled at -12°C, and stir vigorously to obtain a cellulose solution with a concentration of 2-4.5wt%; dissolve 2-5g of copper nitrate in the above cellulose solution and disperse it evenly, then add 0.6-1.5g of glutaraldehyde, stir at room temperature for 30-60 minutes, and then ultrasonically treat for 15-30 minutes, wash with deionized water to obtain a cellulose hydrogel, and remove the contained water by supercritical drying or freeze drying to obtain a cellulose aerogel;
[0025] S2.2: The obtained nanocellulose aerogel is immersed in 30-50 mL of 15-18 mg / mL 2-methylimidazole solution overnight for 12-14 hours, and then rinsed with deionized water for multiple times to obtain a composite hydrogel, and then supercritical drying or freeze-drying is performed to remove the contained water to obtain a three-dimensional porous composite aerogel.
[0026] Preferably, the nitrogen-containing six-membered heterocyclic catalyst is prepared by replacing the N-hydroxyphthalimide benzene ring with a pyridine ring and a pyrazine ring.
[0027] Compared with the prior art, the present invention provides a formula of a carbon dioxide absorbent and a preparation method thereof, which has the following beneficial effects:
[0028] The present invention prepares modified nanocellulose by correspondingly treating waste plants, and provides abundant pores and surface active sites. The metal organic framework has a high specific surface area and porosity. The synergistic effect of the two greatly increases the absorbent and CO 2 The contact area is increased significantly, thereby significantly improving the absorption capacity and reducing the overall cost of the absorbent while ensuring performance. The absorption efficiency of the absorbent is further improved by adding graphene, 1-ethyl-3-methylimidazolium glycine salt ionic liquid, activated carbon, diethylenetriamine, alkali metal salts, sodium dodecyl sulfate, etc. It can be applied to CO2 from various industrial emission sources. 2 Capture, and still maintain stable absorption performance under harsh working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a flow chart of the method mentioned in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0031] The present invention prepares modified nanocellulose by correspondingly treating waste plants, and provides abundant pores and surface active sites. The metal organic framework has a high specific surface area and porosity. The synergistic effect of the two greatly increases the absorbent and CO 2 The contact area is increased significantly, thereby significantly improving the absorption capacity and reducing the overall cost of the absorbent while ensuring performance. The absorption efficiency of the absorbent is further improved by adding graphene, 1-ethyl-3-methylimidazolium glycine salt ionic liquid, activated carbon, diethylenetriamine, alkali metal salts, sodium dodecyl sulfate, etc. It can be applied to CO2 from various industrial emission sources. 2 Capture, and can still maintain stable absorption performance under harsh working conditions. Specifically include the following.
[0032] Embodiment 1:
[0033] See also Figure 1 The present invention provides a formula of a carbon dioxide absorbent, which comprises, by weight percentage: CO 2The formula of the absorbent includes, by weight percentage: 10% modified nanocellulose, 15% metal organic framework, 3% graphene, 15% 1-ethyl-3-methylimidazolium glycine salt ionic liquid, 5% activated carbon, 10% diethylenetriamine, 8% alkali metal salt, 0.3% sodium dodecyl sulfate, 30% water and 15% ethanol. 0.15% acid-base indicator, such as phenolphthalein or a mixture of phenolphthalein, didan yellow, chrome azure, etc., is also added for color indication. Alkali metal salts are made by mixing nitrates and carbonates, with a molar ratio of nitrates to carbonates of 2; the types of nitrates and carbonates are not less than two. Such as sodium nitrate, potassium nitrate; sodium carbonate potassium carbonate. Modified nanocellulose provides abundant pores and surface active sites, and the metal organic framework has a high specific surface area and porosity. The synergistic effect of the two can greatly increase the absorbent and CO 2 The contact area of 1-ethyl-3-methylimidazolium glycinate is increased significantly, thereby significantly improving the absorption capacity. The addition of graphene further enhances the conductivity and structural stability of the material, which helps to improve the absorption efficiency. 1-ethyl-3-methylimidazolium glycinate ionic liquid has a unique ionic structure and chemical properties, which can 2 Selective adsorption reduces the adsorption of other gases, thereby improving the purity of separation. The microporous structure and surface chemical properties of activated carbon also help to selectively capture CO 2 . Diethylenetriamine and CO 2 The chemical bonds formed are relatively weak, which reduces the energy required for the absorbent to be regenerated. The presence of alkali metal salts may adjust the chemical environment of the absorbent, optimize the regeneration conditions, and reduce energy consumption. Sodium dodecyl sulfate can improve the compatibility and dispersibility between the components and enhance the overall stability of the absorbent. The synergistic effect of multiple components enables the absorbent to maintain good absorption performance after multiple cycles, reducing the cost and environmental pressure caused by frequent replacement due to the attenuation of absorbent performance.
[0034] A method for preparing a formula of a carbon dioxide absorbent comprises the following steps:
[0035] S1: Preparation of biomaterial-modified nanocellulose:
[0036] S1.1: The cellulose-rich plant waste was vacuum dried at 105°C for 2 h, ground by a grinder, and the plant powder was soaked in 10% K 2 OH solution, and heated at 60°C, and then fully washed with distilled water, and then dried at 70°C, and then the dried matter was immersed in a hydrogen peroxide solution, and then fully washed with distilled water, and then dried at 70°C to obtain plant powder;
[0037] S1.2: Add the plant powder to water at a material-liquid ratio of 1:80-120 g / mL, then add 0.02 g of pyrroline nitroxide free radical and 0.2 g of nitrogen-containing six-membered heterocyclic catalyst, start the reaction by adding 10-15% hydrogen peroxide solution under ultrasonic stirring, and use 0.5% K 2 OH solution to adjust the pH value and keep it at 10.3-10.7 without consuming K 2 In the presence of OH, ethanol is added to stop the reaction, and then stirred for 15 to 25 minutes. The final product is washed with deionized water by continuous centrifugation at 3000 to 3500 r / min for 10 to 15 minutes until it is neutral; the recovered supernatant becomes a nanocellulose water suspension, which is freeze-dried to obtain cellulose nanofibers;
[0038] S1.3: sterilizing the MRS culture medium with an autoclave at 120-125°C, activating and culturing Lactobacillus plantarum at 37°C, adding the cellulose nanofibers and the bacterial activation solution to the sterile culture solution, and then subjecting the culture solution to differential centrifugation at 3000-3500 r / min to obtain modified cellulose nanofibers;
[0039] Nanocellulose has a high specific surface area and good pore structure, which can provide more active sites to load and absorb components. Vitamin-rich plant waste, such as cotton, ramie, flax, jute, bamboo, wheat straw, rice straw, wood, etc., are rich in cellulose. The waste of this type of plant is huge in volume and has a low utilization rate. The extraction and preparation of nanocellulose based on its waste can reduce the preparation cost and improve the utilization rate of agricultural waste. Nanocellulose is also modified by plant lactobacillus to ensure the green safety of cellulose and form nanocellulose materials with excellent performance.
[0040] S2: Synthesis of metal-organic frameworks and their incorporation into modified nanocellulose:
[0041] S2.1: Dissolve 2-4.5g of cellulose in a mixed solution of sodium hydroxide / urea / water in a mass ratio of 7:12:81 precooled at -12°C, and stir vigorously to obtain a cellulose solution with a concentration of 2-4.5wt%; dissolve 2-5g of copper nitrate in the above cellulose solution and disperse it evenly, then add 0.6-1.5g of glutaraldehyde, stir at room temperature for 30-60 minutes, and then ultrasonically treat for 15-30 minutes, wash with deionized water to obtain a cellulose hydrogel, and remove the contained water by supercritical drying or freeze drying to obtain a cellulose aerogel;
[0042] S2.2: The obtained nanocellulose aerogel is immersed in 30-50 mL of 15-18 mg / mL 2-methylimidazole solution overnight for 12-14 hours, and then rinsed with deionized water for multiple times to obtain a composite hydrogel, and then supercritical drying or freeze-drying is performed to remove the contained water to obtain a three-dimensional porous composite aerogel.
[0043] Nanocellulose is combined with metal organic frameworks. Metal organic frameworks have high specific surface area and rich pore structure, which can provide a large number of adsorption sites. After combining with nanocellulose, the adsorption capacity of the overall material for carbon dioxide can be increased and the adsorption efficiency can be improved. The interaction between nanocellulose and metal ions can be utilized to help preferentially adsorb carbon dioxide in complex gas mixtures and improve the purity of separation. Nanocellulose has good mechanical properties and stability. After combining with metal organic frameworks, the structural stability of the composite material can be enhanced to prevent the structural collapse and agglomeration of the metal organic framework during adsorption and desorption. The fiber network structure of nanocellulose can provide channels for gas diffusion and improve the mass transfer process. This helps carbon dioxide reach the adsorption sites of the metal organic framework faster and increase the adsorption rate. Nanocellulose usually comes from renewable resources, is relatively low in cost and environmentally friendly. Combining with metal organic frameworks can reduce the cost of the overall material to a certain extent, while reducing dependence on non-renewable resources. Combining metal organic frameworks with nanocellulose has great potential in the field of carbon dioxide adsorption and separation, and can provide new ideas and approaches for the development of efficient, economical and sustainable carbon dioxide capture and separation technologies.
[0044] S3: 1-ethyl-3-methylimidazolium glycine salt ionic liquid, diethylenetriamine, graphene, alkali metal salt, water and ethanol were mixed according to the formula ratio, and the complex prepared in S2 was added to the mixed solution, and stirred at room temperature for 1 to 3 hours to prepare CO 2 Absorbent.
[0045] Embodiment 2:
[0046] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, the difference is that the modified nanocellulose is replaced by nanocellulose, and the preparation method is the same as that in Example 1.
[0047] Embodiment 3:
[0048] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the content of modified nanocellulose is 0 / 3% / 5% / 15% / 18%. The preparation method is the same as that in Example 1.
[0049] Embodiment 4:
[0050] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the content of the metal organic framework is 0 / 5% / 10% / 20% / 25%. The preparation method is the same as that in Example 1.
[0051] Embodiment 5:
[0052] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the graphene content is 0 / 0.5% / 1% / 5% / 8%. The preparation method is the same as that in Example 1.
[0053] Embodiment 6:
[0054] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the content of 1-ethyl-3-methylimidazolium glycine salt ionic liquid is 0 / 5% / 10% / 20% / 25%. The preparation method is the same as that in Example 1.
[0055] Embodiment 7:
[0056] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the activated carbon content is 0 / 0.5% / 1% / 10% / 15%. The preparation method is the same as that in Example 1.
[0057] Embodiment 8:
[0058] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the content of diethylenetriamine is 0 / 1% / 5% / 15% / 20% / 25%. The preparation method is the same as that in Example 1.
[0059] Embodiment 9:
[0060] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the content of the alkali metal salt is 0 / 1% / 5% / 10% / 15%. The preparation method is the same as that in Example 1.
[0061] Embodiment 10:
[0062] The CO prepared in this example and in Example 1 2 The addition ratio of the absorbent is the same, except that the content of sodium dodecyl sulfate is 0 / 0.05% / 0.1% / 0.5% / 0.8%. The preparation method is the same as that in Example 1.
[0063] The CO prepared in Examples 1 to 10 was tested by adding 0.15% acid-base indicator to distilled water as a control group.2 The absorbent carries out CO 2 Absorption test, based on 722 visible spectrophotometer to measure and calculate the color change of the absorbent, and use the value 1-5 to quantify the color change of the absorbent according to the calculation result, from small to large, corresponding to the obvious degree of change, the larger the value, the more obvious, the specific results can be referred to Table 1:
[0064] Table 1 CO in Examples 1 to 10 2 Absorption performance test results of absorbent
[0065]
[0066]
[0067]
[0068] The table shows the CO 2 The absorbent reacts with CO under the same environment. 2 The absorption test results of Example 1 show that the CO 2 Absorbent for CO 2 The absorption effect is the best, and it can also absorb CO under different temperature conditions and pressure conditions. 2 The absorption effect of the absorbent is tested.
[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A formula of a carbon dioxide absorbent, characterized in that: The invention comprises, by weight percentage, 5-15% of modified nanocellulose, 10-20% of metal organic framework, 1-5% of graphene, 10-20% of 1-ethyl-3-methylimidazolium glycine salt ionic liquid, 1-10% of activated carbon, 5-20% of diethylenetriamine, 5-10% of alkali metal salt, 0.1-0.5% of sodium dodecyl sulfate, 20-40% of water and 10-20% of ethanol.
2. The formulation of a carbon dioxide absorbent according to claim 1, characterized in that: 0.02-0.20% of an acid-base indicator is also added to the formula.
3. The formulation of a carbon dioxide absorbent according to claim 1, characterized in that: The alkali metal salt is prepared by mixing nitrate and carbonate, the molar ratio of the nitrate to the carbonate is 1.5-2; and the types of the nitrate and the carbonate are not less than two.
4. The formulation of a carbon dioxide absorbent according to claim 1, characterized in that: The nanocellulose in the modified nanocellulose is extracted from cellulose-rich waste plants through a TEMPO oxidation method.
5. The formulation of a carbon dioxide absorbent according to claim 1, characterized in that: The modified nanocellulose is modified by using Lactobacillus plantarum as a modification tool.
6. A method for preparing a formulation of a carbon dioxide absorbent according to any one of claims 1 to 5, characterized in that: The steps include: S1: Preparation of biomaterial-modified nanocellulose: S1.1: Dry the cellulose-rich plant waste in a vacuum at 105°C for 2 hours, grind it with a grinder, soak the plant powder in a 10% K2OH solution, heat it at 60°C, wash it with distilled water, dry it at 70°C, soak the dried material in a hydrogen peroxide solution, wash it with distilled water, and dry it at 70°C to obtain the plant powder; S1.2: Add plant powder to water at a solid-liquid ratio of 1:80-120 g / mL, then add 0.02 g of pyrroline nitrogen oxide free radical and 0.2 g of nitrogen-containing six-membered heterocyclic catalyst, start the reaction by adding 10-15% hydrogen peroxide solution under ultrasonic stirring, adjust the pH value with 0.5% K2OH solution, and keep the pH value at 10.3-10.7, add ethanol to stop the reaction without consuming K2OH, and then stir for 15-25 minutes, wash the final product with deionized water by continuous centrifugation at 3000-3500 r / min for 10-15 minutes until it is neutral; the recovered supernatant becomes a nanocellulose aqueous suspension, which is freeze-dried to obtain cellulose nanofibers; S1.3: sterilizing the MRS culture medium with an autoclave at 120-125°C, activating and culturing Lactobacillus plantarum at 37°C, adding the cellulose nanofibers and the bacterial activation solution to the sterile culture solution, and then subjecting the culture solution to differential centrifugation at 3000-3500 r / min to obtain modified cellulose nanofibers; S2: Synthesize metal-organic frameworks and combine them with modified nanocellulose; S3: Mix 1-ethyl-3-methylimidazolium glycine salt ionic liquid, diethylenetriamine, graphene, alkali metal salt, water and ethanol according to the formula ratio, add the complex prepared in S2 to the mixed liquid, and stir at room temperature for 1 to 3 hours to prepare a CO2 absorbent.
7. The method for preparing a carbon dioxide absorbent formulation according to claim 6, characterized in that: The S2 is specifically as follows: S2.1: Dissolve 2-4.5g of cellulose in a mixed solution of sodium hydroxide / urea / water in a mass ratio of 7:12:81 precooled at -12°C, and stir vigorously to obtain a cellulose solution with a concentration of 2-4.5wt%; dissolve 2-5g of copper nitrate in the above cellulose solution and disperse it evenly, then add 0.6-1.5g of glutaraldehyde, stir at room temperature for 30-60 minutes, and then ultrasonically treat for 15-30 minutes, wash with deionized water to obtain a cellulose hydrogel, and remove the contained water by supercritical drying or freeze drying to obtain a cellulose aerogel; S2.2: The obtained nanocellulose aerogel is immersed in 30-50 mL of 15-18 mg / mL 2-methylimidazole solution overnight for 12-14 hours, and then rinsed with deionized water for multiple times to obtain a composite hydrogel, and then supercritical drying or freeze-drying is performed to remove the contained water to obtain a three-dimensional porous composite aerogel.
8. The method for preparing a carbon dioxide absorbent formulation according to claim 6, characterized in that: The nitrogen-containing six-membered heterocyclic catalyst is prepared by replacing the N-hydroxyphthalimide benzene ring with a pyridine ring and a pyrazine ring.